On being a teacher : the human dimension - Kottler, Jeffrey A.; Zehm, Stanley J.; Kottler, Ellen (California : Corwin Press, 2005)
The authors help preservice, beginning, and veteran teachers discover their own special traits that make them superlative teachers.
Includes bibliographical references (p. 159-167) and index.
Keywords: Teaching; Motivation in education; Teachers